Evaluation of Public Acceptance of Digital ID Cards: Legal and Technological Implications in Indonesian Public Administration - Lestari, Mugi; Agung S, M Panji (Communication in Research and Publications (CRP), 2024)
The implementation of a digital identity system in Indonesia, specifically through the introduction of digital ID cards, represents a significant milestone in the country's public administration. This policy aims to streamline administrative processes, enhance service access, and ensure more efficient management of citizen data. However, the shift to digital identities presents challenges related to personal data protection, technological infrastructure, and public acceptance. This study explores the implications of the digital identity policy, focusing on legal frameworks, public reception, and the protection of personal data. Using a qualitative approach, the study analyzes key findings from interviews, document reviews, and observations, highlighting critical issues such as the security of biometric data, the integration of digital identity systems across public services, and the public's understanding of digital rights. The study concludes with policy recommendations aimed at strengthening data protection laws, improving infrastructure in underserved areas, and fostering greater public awareness to ensure a successful transition to a digital identity system in Indonesia.